PREREQUISITES FOR THE DEVELOPMENT OF PROJECT MANAGEMENT PRACTICES IN DOMESTIC OIL AND GAS ENTERPRISES IN THE CONTEXT OF THE GREEN TRANSITION - Zapukhliak, Ivanna; Kuznietsov, Andrii (Current Problems of Sustainable Development, 2026)
The article examines the prerequisites for the formation and development of project management practices in the activities of domestic oil and gas enterprises under the conditions of the green transition. The relevance of the study is determined by the need to adapt the oil and gas sector to contemporary challenges associated with the transformation of the global energy system, the implementation of decarbonization policies, increasingly stringent environmental requirements, and the consequences of the full-scale war, which has significantly affected Ukraine’s energy infrastructure. It is established that one of the key external drivers of project activity development is the European Green Deal, which envisages achieving climate neutrality, expanding renewable energy sources, improving energy efficiency, and implementing low-carbon technologies. The study substantiates that Ukraine’s integration into the European energy space creates additional incentives for the implementation of investment, innovation, and organizational projects in the oil and gas industry. The current operating conditions of domestic oil and gas enterprises are analyzed. Particular attention is paid to wartime risks, damage to production and gas transmission infrastructure, a decline in domestic natural gas production, the need to diversify energy supply sources, and increased natural gas imports. At the same time, positive trends related to the development of international cooperation, access to LNG markets, attraction of investments in subsoil use, and the introduction of modern technologies into production processes are identified. The study highlights the main internal prerequisites for the development of project activities, including infrastructure restoration and modernization, implementation of innovative technologies, business diversification, attraction of investment resources, decarbonization measures, development of international partnerships, digitalization of management processes, improvement of risk management, and transition to a project-oriented management model. It is argued that project management is becoming an essential tool for implementing transformational changes, increasing adaptability, ensuring sustainable development, and strengthening the long-term competitiveness of domestic oil and gas enterprises in the context of the green transition.